Critical periods of weed control in naturally green colored cotton BRS Verde - Cardoso, Gleibson D.; Alves, Pedro L. C. A. [UNESP]; Severino, Liv S.; Vale, Leandro S. (Elsevier B.V., 2011)
Cotton with naturally colored fiber is increasing as a commercial crop due specially to its textile processing with reduced environmental impact, as dying is not necessary. The critical period of weed control and the weed community were studied in a field with the naturally green colored fiber cv. BRS Verde cultivated in Missao Velha, Brazil. Without weed control during all the cycle, a reduction of 82.9% in yield was observed. The critical period of weed control was between 31 and 74 days after emergence for a reduction of 5% in yield. The weed community was composed of 21 species, with higher relative importance and dominance of monocotyledonous species. The beginning of the critical period was found to be more influential on yield than the ending. Thus, defining the right moment to start weed control can be more important to yield than determining the moment to cease it. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Gossypium hirsutum; Weed community; Fiber; Textile